2017
DOI: 10.1111/1468-2427.12545
|View full text |Cite
|
Sign up to set email alerts
|

Fast Parallels? Contesting Mobile Policy Technologies

Abstract: This article extends recent examinations of incomplete or disrupted policy mobility by examining the politically volatile case of policies to manage the regional impacts of decarbonization in Australia. The article's extended case study shows how political interests differently incorporated figments of circulating policy into longstanding debates and how more‐than‐local political networks defeated an antipolitical, technocratic exercise in ‘new regional’ governance. ‘Follow the policy’ methods could not have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Mobility can be defined as a change of position in a specific space (Jöns et al, 2017), and knowledge becomes mobile through people and processes that enable knowledge to circulate (Weller, 2017).…”
Section: Mobility Of Futures Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Mobility can be defined as a change of position in a specific space (Jöns et al, 2017), and knowledge becomes mobile through people and processes that enable knowledge to circulate (Weller, 2017).…”
Section: Mobility Of Futures Knowledgementioning
confidence: 99%
“…Knowledge-mobilizing situations included both formal and informal meetings, and emails were also sent and workshop material distributed. Futures knowledge became mobile through processes and individuals when they thought, discussed and acted in their own organizations (Weller, 2017). Some participants reported that they had already used the futures knowledge in their organizations, for example, in strategic planning.…”
Section: Mobility Of Futures Knowledgementioning
confidence: 99%
“…Within the then-ruling federal Labor party, support for the CEF and the Gillard leadership hinged on delivering a just transition in the Valley. Yet there was little knowledge and no consensus on what a just transition might entail (Weller, 2017a).…”
Section: The Latrobe Valley In Contextmentioning
confidence: 99%
“…Given Australia's institutional arrangements, framing the problem as being about regional futures rather than as about closing coal-fired power stations made the problem more complex, more politicized and more uncertain than would otherwise have been the case. This is not to deny the existence of local disputes about how best to tackle the Valley's immediate problems (see Weller, 2017a), but rather to suggest that their apparent intractability stems from the realities of the area's material conditions and the implausibility of the proposition that market forces could offer a remedy.…”
Section: Imagining Transitionmentioning
confidence: 99%
See 1 more Smart Citation